Does Forest Resource Protection Under the Carbon Neutrality Target Inhibit Economic Growth? Evidence of Poverty-Stricken County From China - Qi, Huibo; Sun, Lei; Long, Fei; Gao, Xiaowei; Hu, Leifang (Frontiers in Environmental Science, 2022)
Given the overlapping characteristics of poverty-stricken counties within key ecological function zones and ecologically fragile areas in China, this paper takes the sample of 393 state-designated poverty-stricken counties from 2011-2018 and uses differences-in-differences model to test the influence of forest resource protection on economic growth and its mechanism under the carbon neutrality target. The empirical research proves how to break the "green paradox" and "poverty curse" in the process of Chinese ecological civilization construction and targeted poverty alleviation, how policy tools integrate emission reductions with carbon-sequestration increase and achieve sustainable development. The results show that: (1) the economic growth of poverty-stricken counties cannot be separated from industrialization, urbanization, and financial system; (2) China's poverty-stricken counties have achieved an initial decoupling of carbon emissions from economic growth; (3) forest resource protection represented by forest coverage and stock changes the carbon emissions through emission reductions with carbon-sequestration increase, and affect the economic growth of poverty-stricken counties; (4) the reduction of total carbon emissions in poverty-stricken counties further enhances the role of forest resource protection in promoting county economic growth. Taking the 13th Five-Year Plan for Eco-environment Protection as the starting point, this research reveals the different paths and impacts selected by Chinese local governments in poverty alleviation.